Pengembangan Media Pembelajaran Adobe Flash Berbasis CAI untuk Pembelajaran IPA di Sekolah Dasar - Edelweis Mustika Puspa; Erwin Rahayu Saputra (Jurnal Sekolah Dasar, 2023)
This study aims to develop an Adobe Flash learning media product based on CAI in Natural Sciences (IPA) subject matter of sound reflection. Science learning media available at this time are less interactive, less able to attract the attention of students so it is necessary to develop learning media because learning media has a very important role in the learning process, especially to attract attention and increase student interest and can assist teachers in conveying material to students to make it easier to understand. These problems can be overcome by developing CAI-based Adobe Flash learning media. The method used in this study is the ADDIE development method with five stages namely analysis, design, development, implementation, and evaluation. The data collection technique used is by interviewing and validating the material experts and media experts. The results of the validation show that the score obtained from the material expert is 86%, while the media expert gives a score of 97.5% so that this media is included in the criteria of being suitable for use without revision to support science learning in elementary schools on sound reflection material. The response of teachers and students to the Adobe Flash learning media is very good and positive, which means that this media is able to help students to better understand sound reflection material.